First Dose Phenomenon in a Scorpion Sting Patient Being Treated with Prazosin: A Case Report - Manik, Reshma; Pashte, Jagruti Arun; Dalal, Varsha Iranna; Bali, Prasad (Journal of Pharmacy Practice and Community Medicine)
Prazosin, an antihypertensive drug, has found prominent importance in managing scorpion envenomation in recent times. It is being used off the label however studies have found to be very effective in the management of scorpion sting. This is a case report of the prazosin-induced first dose phenomenon in a 4-year-old patient treated for scorpion sting. In hypertensive patients, the first dose phenomenon is a widely reported adverse effect due to prazosin however in scorpion sting patients it is rarely reported. A sudden fall in blood pressure can be life-threatening, more so in the pediatric population. Educating the rural public about the importance of taking medical consultation for a scorpion sting, availability of treatment, and protocol for the management of the scorpion sting is the need of the hour.
Keywords: First dose phenomenon; Prazosin; Scorpion sting; Patient Education.